Porphyrios, contra Christianos: neue Sammlung der Fragmente, Testimonien und Dubia mit Einleitung, Übersetzung und Anmerkungen - Becker, Matthias; Porphyrius (Texte und Kommentare, 2016)
A hundred years after Adolf von Harnack's first edition of Porphyry's Contra Christianos (1916) this work presents a new collection of the fragments and testimonia with an introduction, a German translation and notes. It is the first German translation of and commentary on Contra Christianos. All texts are newly arranged. For the first time ever, texts which cannot be securely attributed to Porphyry (dubia) are presented in a separate section.
Keywords: Hochschulschrift; Kommentar; Quelle; Geschichte 270-303; Polemik; Christentum; Porphyrius / Contra Christianos